2013
DOI: 10.1016/j.jcps.2013.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Taking a shine to it: How the preference for glossy stems from an innate need for water

Abstract: Human beings are attracted to glossy objects. However, the investigation of whether this preference for glossy is a systematic bias, and the rationale for why, has received little or no attention. Drawing on an evolutionary psychology framework, we propose and test the hypothesis that the preference for glossy stems from an innate preference for fresh water as a valuable resource. In a set of six studies we demonstrate the preference for glossy among both adults and young children (studies 1A, 1B and 2) ruling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
70
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(74 citation statements)
references
References 86 publications
3
70
1
Order By: Relevance
“…This finding is in contrast with research on non-food objects, which suggests that a glossy surface of such an object is positively related to luxury and consequently conveys an image of greater quality [28]. In a non-food context, this preference for glossiness is attributed to an innate need for water [24]. In a (perishable) food context, research by Murakoshi et al [29], confirmed the positive effect of glossiness by demonstrating that glossiness signals freshness of the food as the glossy surface is an indicator of water content.…”
Section: Theoretical and Practical Contributionscontrasting
confidence: 87%
See 3 more Smart Citations
“…This finding is in contrast with research on non-food objects, which suggests that a glossy surface of such an object is positively related to luxury and consequently conveys an image of greater quality [28]. In a non-food context, this preference for glossiness is attributed to an innate need for water [24]. In a (perishable) food context, research by Murakoshi et al [29], confirmed the positive effect of glossiness by demonstrating that glossiness signals freshness of the food as the glossy surface is an indicator of water content.…”
Section: Theoretical and Practical Contributionscontrasting
confidence: 87%
“…In line with this finding, we believe that a glossy package serves as a cue to evaluate the product that is inside. While previous research in a non-food context links the preference for glossy to an innate need for water [24], we hypothesize that, in a food context, a glossy surface may also remind consumers of grease. In other words, we believe that the positive association between package glossiness and greasiness of the product might exist because fat and glossiness share some exterior resemblance.…”
Section: Glossy Versus Matte Packaging Materialsmentioning
confidence: 83%
See 2 more Smart Citations
“…Much of this work focused on vision. Extending this body of work, Meert, Pandelaere, and Patrick (2014‐‐in this issue) find that adults as well as children prefer glossy objects over matte objects. They argue that this preference reflects an association of water and glossy surfaces, suggesting that it may be driven by the importance of water in the development of the species.…”
Section: Sensory Experience Mental Simulation and Stimulus Attributesmentioning
confidence: 67%